2022
DOI: 10.1002/btm2.10328
|View full text |Cite
|
Sign up to set email alerts
|

An injectable gelatin/sericin hydrogel loaded with human umbilical cord mesenchymal stem cells for the treatment of uterine injury

Abstract: Abnormal endometrial receptivity is a major cause of the failure of embryo transplantation, which may lead to infertility, adverse pregnancy, and neonatal outcomes. While hormonal treatment has dramatically improved the fertility outcomes in women with endometriosis, a substantial unmet need persists in the treatment. In this study, methacrylate gelatin (GelMA) and methacrylate sericin (SerMA) hydrogel with human umbilical cord mesenchymal stem cells (HUMSC) encapsulation was designed for facilitating endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 54 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Currently, the clinical acquiescence of stem cell Frontiers in Physiology frontiersin.org therapy mostly uses local direct injection. However, when the wound injury is large, direct injection will lead to a low local cell retention rate, reduce the biological activity of MSCs, and hinder the effect of stem cell therapy (Gill et al, 2018;Chen et al, 2023). Recent studies have shown that hydrogels have good biocompatibility and unique micropore structure and are good carriers for drugs and cells (Wang et al, 2020;Zhao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the clinical acquiescence of stem cell Frontiers in Physiology frontiersin.org therapy mostly uses local direct injection. However, when the wound injury is large, direct injection will lead to a low local cell retention rate, reduce the biological activity of MSCs, and hinder the effect of stem cell therapy (Gill et al, 2018;Chen et al, 2023). Recent studies have shown that hydrogels have good biocompatibility and unique micropore structure and are good carriers for drugs and cells (Wang et al, 2020;Zhao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments displayed increased thickness of the endometrium, decreased interstitial fibrosis, and fostered receptivity to embryo transfer. Thus, the developed hydrogel stands favorable for repairing damaged endometrium and promoting fertility outcomes [197].…”
Section: Other Tissuesmentioning
confidence: 99%
“…84 SerMA hydrogels were also reported as a material with potential to regenerate damaged endometrium, as a result of its encapsulation ability of human umbilical cord mesenchymal stem cells. 85 SS can also be functionalized with urethane methacryloyl groups to produce a SS urethane methacryloyl, resulting in increased hydrophilicity when compared to SerMA. 86 The hydrogel was characterized by a mass loss of <25% after 21 days of incubation, demonstrating suitability for longer-term support for skin regeneration.…”
Section: Tissue Engineering and Regenerative Medicinementioning
confidence: 99%